Michelson interferometer for phase shifting interferometry with a liquid crystal retarder - Yanely B. Machuca-Bautista (Elsevier, 2021)
We propose an interferometric system to measure phase objects using electronic phase shifting techniques. The experimental setup is based on a polarization Michelson type interferometer, where a liquid crystal retarder is placed at the entrance pupil as a phase shifter. First, the interferometric setup is used for the calibration of a phase-shifting device. Then, the interferometer is used to measure a phase object employing generalized phase-shifting algorithms to retrieve the phase solving the nonlinear response of the liquid crystal retarder. Experimental results are presented, and the advantages and limitations of the proposed technique are also discussed.